Managing Systemic Banking Crises : New Lessons and Lessons Relearned - Moretti, Marina (Departmental Papers; Departmental Paper ;, 2020)
This paper updates the IMF's work on general principles, strategies, and techniques from an operational perspective in preparing for and managing systemic banking crises in light of the experiences and challenges faced during and since the global financial crisis. It summarizes IMF advice concerning these areas from staff of the IMF Monetary and Capital Markets Department (MCM), drawing on Executive Board Papers, IMF staff publications, and country documents (including program documents and technical assistance reports). Unless stated otherwise, the guidance is generally applicable across the IMF membership.